Pengaruh Harga Dan Kualitas Produk Terhadap Minat Beli Sikncare Merek Skintific (Studi kasus pada Mahasiswa Fakultas Ekonomi Universitas Sumatera Barat) - Asrul; Yasnida (Jurnal Ekonomi dan Bisnis Digital, 2024)
This research is entitled The Influence of Product Price and Quality on Interest in Buying Skintific Brand Skincare (Case Study of Students at the Faculty of Economics, University of West Sumatra), this research is motivated by the background of many young people, especially women, who use skincare, especially students who always want to look their best at every opportunity. This Skintific product has become a hot topic on social media, there are many discounts offered and the prices are quite competitive, but there are also many people interested in it. This research uses primary data by distributing questionnaires to students and the data is processed using the SPSS application. In this research, it was found that partially price had a significant effect on students' buying interest, partially product quality had a significant effect on students' buying interest. Simultaneously, price and product quality have a significant effect on students' buying interest.